2019
DOI: 10.1108/jcom-11-2018-0119
|View full text |Cite
|
Sign up to set email alerts
|

Influencer marketing

Abstract: Purpose The purpose of this paper is to investigate the effects of a particular form of sponsorship disclaimer in sponsored content by social media influencers (SMIs), namely a sponsorship compensation justification disclosure. A sponsorship compensation justification disclosure explains why influencers and brands engage in sponsorship collaborations by providing a normative reason that justifies the existence and dissemination of sponsored content. Design/methodology/approach An experimental design was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 53 publications
3
38
0
1
Order By: Relevance
“…These results show that disclosure under various conditions can negatively influence the persuasive effect of a SMI's messages (Boerman and Van Reijmersdal, 2020). Moreover, the perceptions of the influencer and the marketing message are moderated by how the disclosure is communicated (Stubb et al, 2019).…”
Section: Social Media Influencers As Hidden Persuadersmentioning
confidence: 76%
“…These results show that disclosure under various conditions can negatively influence the persuasive effect of a SMI's messages (Boerman and Van Reijmersdal, 2020). Moreover, the perceptions of the influencer and the marketing message are moderated by how the disclosure is communicated (Stubb et al, 2019).…”
Section: Social Media Influencers As Hidden Persuadersmentioning
confidence: 76%
“…In addition, these insights have important practical implications for implementing disclosures. Previous studies on content characteristics found mixed effects (Stubb, Nystr€ om, and Coliander 2019;Tewksbury, Jensen, and Coe 2011;. In this meta-analysis, we distinguish three major types of content information: mentioning the brand, mentioning the word advertising, and mentioning persuasive intent, all of which are likely to predict disclosure effectiveness (van Reijmersdal 2016).…”
Section: Moderators Of Effects Of Disclosing Sponsored Contentmentioning
confidence: 99%
“…When making purchase decisions, consumers engage more with their peers than with celebrities as a reference group across digital platforms (Main, 2017). The rise of influencer marketing on social media, which focuses on connecting companies with their target market through influential users (Stubb, Nyström, & Colliander, 2019), symbolizes consumersʼ tendency to seek information from individuals with whom they have a higher level of interpersonal closeness than with celebrities (Hahn & Lee, 2014). Within the endorsement spectrum, influencer marketing yields several communicative advances, such as facilitating influencer-follower interactions that are more approachable (Schwemmer & Ziewiecki, 2018) and intimate compared with other types of endorsement channels (Berryman & Kavka, 2017).…”
Section: Influencer Marketing and Consumer Trustmentioning
confidence: 99%